Correction of depression‐associated circadian rhythm abnormalities is associated with lithium response in bipolar disorder. (6th December 2021) - Federoff, Monica; McCarthy, Michael J.; Anand, Amit; Berrettini, Wade H.; Bertram, Holli; Bhattacharjee, Abesh; Calkin, Cynthia V.; Conroy, Carla; Coryell, William H.; D'Arcangelo, Nicole; DeModena, Anna; Fisher, Carrie; et al.
Abstract: Background: Bipolar disorder (BD) is characterized by episodes of depression and mania and disrupted circadian rhythms. Lithium is an effective therapy for BD, but only 30%–40% of patients are fully responsive. Preclinical models show that lithium alters circadian rhythms. However, it is unknown if the circadian rhythm effects of lithium are essential to its therapeutic properties. Methods: In secondary analyses of a multi‐center, prospective, trial of lithium for BD, we examined the relationship between circadian rhythms and therapeutic response to lithium. Using standardized instruments, we measured morningness, diurnal changes in mood, sleep, and energy (circadian rhythm disturbances) in a cross‐sectional study of 386 BD subjects with varying lithium exposure histories. Next, we tracked symptoms of depression and mania prospectively over 12 weeks in a subset of 88 BD patients initiating treatment with lithium. Total, circadian, and affective mood symptoms were scored separately and analyzed. Results: Subjects with no prior lithium exposure had the most circadian disruption, while patients stable on lithium monotherapy had the least. Patients who were stable on lithium with another drug or unstable on lithium showed intermediate levels of disruption. Treatment with lithium for 12 weeks yielded significant reductions in total and affective depression symptoms. Lithium responders (Li‐Rs) showed improvement in circadian symptoms of depression, but non‐responders did not. There was no difference between Li‐Rs and nonresponders in affective, circadian, or total symptoms of mania. Conclusions: Exposure to lithium is associated with reduced circadian disruption. Lithium response at 12 weeks was selectively associated with the reduction of circadian depressive symptoms. We conclude that stabilization of circadian rhythms may be an important feature of lithium's therapeutic effects. Clinical Trials Registry: NCT0127253.